Salvation of severely fractured anterior tooth: An orthodontic approach - Ayer, Ashok; Gyawali, Rajesh; Bhattarai, Bahusan; Suwal, Pramita (Journal of College of Medical Sciences-Nepal, 2016)
Restoration of severely fractured teeth presents a challenge to the endodontist and may require an interdisciplinary approach for proper management. When the available crown structure is less, orthodontic forced extrusion is the option where the coronal root structure is exposed for proper restoration. This report describes the management of severely fractured maxillary right lateral incisor with extensive loss of coronal structure and fracture line extending below gingival margin. Endodontic treatment of the fractured tooth was followed by controlled orthodontic extrusion to expose fracture margin and providing sufficient coronal tooth structure to support the prosthesis. Orthodontic extrusion may be considered as a viable option for the salvation of fractured anterior teeth. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 35-38